Evaluasi Penggunaan Aplikasi Akuntansi oleh Bendaharawan Sebelum dan Sesudah Penerapan Sistem Keuangan Desa (Siskeudes) di Kecamatan Bengkalis - Rozita Rozita; Nur Anita (Politeknik Negeri Bengkalis, 2020)
This study aims to describe the use of accounting applications by treasurers through an evaluation of the performance of the village Treasurer in the Bengkalis district before and after the application of the village financial system (SISKEUDES). The sample in this study is the Village Treasurer in Bengkalis district, the type of research used is qualitative research. The data source in this study is the primary data. Data collection techniques are done using interview techniques. The data analysis technique used is descriptive analysis. The results of this study indicate that the performance of the village treasurer before the implementation of SISKEUDES in indicators of quantity, quality of work, costs, commitment and cooperation is quite good, because the Treasurer can complete tasks and work according to Permendagri Number 113 of 2014, but the punctuality indicators are quite not good. While after applying SISKEUDES Village Treasurer's performance on indicators of quantity, quality of work, cost, commitment and cooperation it is also quite good because the Treasurer can complete tasks and work according to the Regulation of the Minister of the Interior Number 20 of 2018, but it is still said that the punctuality indicator is missing well.